Cloud Requirement and Cloud Analysis - Singh, Gurdev; Singh, Harmandeep; Singh, Amandeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cloud computing is model which uses combine concept of software-as-a-service and œutility computing ,provide convenient and on-demand services to requested end users. Cloud Engineering is a discipline that uses combination of the business and technology thinking for purposes of engineering a cloud. The structure and principles of cloud engineering plays an important role for the engineering of usable and economic cloud. The cloud development life cycle (CDLC) is the one of the component in structure of cloud engineering with Base, Tools & Techniques and Management components. CDLC is the iterated life cycle model for development, deployment and delivery of cloud. CDLC consists of six phases that are flexible, isolated executable and having feedback. The work on this paper focuses on the Understanding Requirement and Analysis phase of the CDLC. This paper lists and discusses the basic, content and operational requirements for the engineering of economic cloud. It also discuses feasibility checks for the requirements. Analysis part of this phase does the analysis of their cloud computing solution with another available computing solution such as grid computing, volunteer computing, utility computing, autonomic computing, client-server model and peer to peer model; and also does cloud planning for cloud implementation phase